To solve the system of equations, we need to substitute the value of y from the second equation into the first equation.
Substituting y = 10 + 4x into the first equation:
8x - 3(10 + 4x) = -22
Distributing:
8x - 30 - 12x = -22
Combining like terms:
-4x - 30 = -22
Adding 30 to each side:
-4x = 8
Dividing by -4:
x = -2
Now, substitute this value of x back into the second equation to solve for y:
y = 10 + 4(-2)
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is x = -2, y = 2.
Solve the system of equations. 8x−3y= −22 y=10+4x (1 point)
1 answer